Senior High School Students’ Order Thinking and Confidence in Solving Math Problems - Aniati, Aniati; Nadirah, Sitti; Ismaya, Bambang; Jenuri, Jenuri; Suwarma, Dina Mayadiana (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study aims to elucidate the correlation between enhancing high-level cognitive thinking skills among school students and their self-assurance when tackling mathematical challenges. Employing a qualitative research approach, specifically the library research method, this investigation entails an in-depth exploration of various scholarly sources, encompassing articles and books, to serve as research data. These sources are directly pertinent to students' sequential thinking proficiency and self-belief in addressing mathematical problems. The outcomes derived from this research substantiate the existence of a discernible association between students and their instructors within the classroom setting. This interplay possesses the potential to exert an influential impact on the students' overall condition and academic achievements. Furthermore, a compelling correlation emerges between these two pivotal factors. Consequently, students with elevated high-level cognitive thinking skills and a corresponding self-assured disposition are inherently predisposed to demonstrating a greater propensity for successfully resolving mathematical challenges. This study highlights the intrinsic connection between students' cognitive capacities and self-confidence levels, underscoring the pivotal role these factors play in their ability to address mathematical problems effectively.